Enthesitis-related arthritis is the most common category of juvenile idiopathic arthritis in Taiwan and presents persistent active disease - Yang-Jen Shih; Yao-Hsu Yang; Chun-Ying Lin; Chia-Ling Chang; Bor-Luen Chiang (BMC, 2019)
Abstract Background Juvenile idiopathic arthritis (JIA) has been categorized into seven different categories according to the International League of Associations for Rheumatology (ILAR) criteria. Enthesitis-related arthritis (ERA) was found to represent the largest category in a Taiwanese cohort study. The aim in this study was to compare the clinical characteristics, treatments, and outcomes of ERA in a single tertiary center in Taiwan, as compared to those of other categories of JIA. Furthermore, we determined patients' characteristics and risk factors that can help assess the outcomes in ERA. Methods A retrospective chart review of all patients with JIA referred to a pediatric rheumatology clinic in the National Taiwan University Hospital between 1993 and 2018 were identified according to ILAR criteria. Outcomes were assessed based on the Wallace criteria to categorize patients into active and non-active, including inactive, remission on medication, and remission off medication, groups. A subset of samples was further tested by DNA sequencing to identify HLA-B27 subtypes. Results One-hundred and eighty-three patients were included in the study, with a mean of 8 years' follow-up. ERA was the single largest category of JIA (39.9%); psoriasis and undifferentiated JIA were both the least common type (0.5%). ERA was male predominant (86%), had a late age of onset (11.0 ± 3.2 years), and the majority of ERA patients was HLA-B27-positive (97%). Of 25 HLA-B27-positive ERA patients checked by HLA-B27 sequencing, 23 were B*27:04 and 2 were B*27:05. ERA patients were significantly less likely to achieve non-active status compared to patients with persistent oligoarthritis (P = 0.036). In terms of treatment response to TNF-α inhibitors in methotrexate-refractory ERA, 26 patients remained active and only 11 patients (30%) achieved a non-active status. Sacroiliitis was a risk factor contributing to poorer treatment response in ERA (P = 0.006). Conclusion ERA represented the most common category of JIA in Taiwan. Those ERA patients with sacroiliitis were likely to have persistent active disease and may require a more aggressive treatment strategy to improve their outcomes.